Narratives of variation in teacher-pupil relationships across a career - Kington, Alison (Ozel Akademi (OZELA), 2012)
This paper reports on the findings of a research study focused on teacher perceptions of their relationships with pupils over three phases of a career. Data collected from thirty primary school teachers using a critical event narrative approach were coded and compared across the three groups of teachers at different points in their careers; 0-7 years, 8-23 years, and over 24 years. The study, based in the United Kingdom, highlighted a complex development amongst teachers which centres on five key areas identified as differentiating between the three career phases; interaction, behaviour, expectations, proximity and control. Results indicate that teachers go through a series of relationship transitions in relation to these five areas, and that these transitions can often confront teachers with conflicting views of what positive teacher-pupil relationships are and create personal dissonance as they try to make sense of their role in these relationships. Based on empirical evidence, this paper argues that positive relationships with pupils are not necessarily associated with experience and that the transitions teachers experience through their career is of concern given the centrality of teacher-pupil relationships to effective teaching.